Optimizing Digital Marketing to Increase the Competitiveness of Small and Medium Enterprises - Asmar Yulastri; Ganefri Ganefri; Elfizon Elfizon; Feri Ferdian; Yudha Fiandra (JTEV (Jurnal Teknik Elektro dan Vokasional), 2025)
This study aims to optimize digital marketing strategies to enhance the competitiveness of Small and Medium Enterprises (SMEs) in Balai Kaliki Tourism Village, Payakumbuh City, West Sumatra. The research is grounded in the crucial role of SMEs in driving local economic development while facing challenges related to limited digital literacy and market access. The study employed Participatory Action Research (PAR), engaging 10 SMEs as both research participants and co-researchers through the stages of problem identification, planning, action, and reflection. The findings indicate that the implementation of social media-based digital marketing, branding, and e-commerce integration significantly improved SMEs’ online visibility, customer engagement, and sales performance, with average sales growth exceeding 40%. Furthermore, SME owners’ confidence and practical skills in managing digital marketing activities increased substantially, from an average of 25–30% before the intervention to over 85% afterwards. The contribution of this study to the field of education lies in strengthening participatory and practice-based learning models, which not only transfer knowledge but also build sustainable digital entrepreneurship capacity. These results highlight the importance of collaborative approaches in entrepreneurship education to reinforce SME competitiveness in the digital transformation era.